Pemberdayaan Kelompok PKK Banjar Tengah Desa Blahbatuh melalui Pelatihan Keterampilan Pembuatan Sabun Padat Berbahan Aloe Vera - Fransiscus Fiano Anthony Kerans; Luh Gde Evayanti; Ni Putu Diah Witari; Komang Trisna Sumadewi; Anak Agung Ayu Asri Prima Dewi; Dewa Ayu Agung Alit Suka Astini; Ida Kurniawati; Gede Agus Surya Pratama (Warmadewa University Press, 2025)
Data from the “Badan Pusat Statistik” states that the production of aloe vera plants in Blahbatuh district, Gianyar regency, is 8644 kg with a harvested area of 2200 m2 in 2019. Aloe vera is not only cultivated on agricultural land, but also becomes a yard plant in the Blahbatuh community, especially Central Banjar. This plant has been known to have bioactive content and antioxidant power, so it has economic use value in the fields of pharmaceuticals, beauty and health. However, knowledge and skills about this potential are still very minimal in the people of Central Banjar. Therefore, this PKM program aims to empower the PKK Women's Group of Central Banjar, Blahbatuh Village, Gianyar, through counselling activities on the importance of skin health and counselling on the benefits of aloe vera plants, as well as training in the skill of making solid soap with aloe vera basics. The program implementation method includes optimization activities on how solid soap-making works before the implementation of training, which is followed by counselling, training and practices of making aloe vera solid soap. The evaluation of the success of the PKM program will be assessed based on the pre-test and post-test values as well as the success of making solid soap independently. The results of the implementation of this program show the enthusiasm and active participation of all participants during the activity. The evaluation of comprehension based on pre-test and post-test scores showed that 8 participants experienced an increase in comprehension with an increase in the average value of participants' overall knowledge by 36.4%. As many as 3 out of 10 partners have also succeeded in making solid soap on the first try. Further assistance is still needed to increase the success of soap making and marketing of soap products so that they can become skills that support the local community's economy.